2021
DOI: 10.47611/jsrhs.v10i2.1442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Improved and Current Vanillin Based Colorimetric Quantification Methods of Triterpenoids

Abstract: The most common colorimetric quantification method for triterpenoids utilizes vanillin in strongly acidic conditions to form a colored adduct with the analyte, and it has gained popularity because it is fast and easy to perform. Nevertheless, the detection range of this assay is limited and it is susceptible to side reactions, which cause an interference in the reading. Here, we quantify the rate of this interference in common solvents, and we present an alternative method to minimize the interference, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…11 Although the main reaction is accompanied by side reactions, the ease of estimation of analytes has made this approach popular. 12 Acidified vanillin assay has been reported for the estimation of saponins, 13 tannins, 14 flavanol derivatives, 15 proanthocyanidins 16 and triterpenoids. 12 Dai et al reported the qualitative and quantitative estimation of azadirachtin related limonoids (Azl) from Azadirachta indica seeds using this assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Although the main reaction is accompanied by side reactions, the ease of estimation of analytes has made this approach popular. 12 Acidified vanillin assay has been reported for the estimation of saponins, 13 tannins, 14 flavanol derivatives, 15 proanthocyanidins 16 and triterpenoids. 12 Dai et al reported the qualitative and quantitative estimation of azadirachtin related limonoids (Azl) from Azadirachta indica seeds using this assay.…”
Section: Introductionmentioning
confidence: 99%
“…12 Acidified vanillin assay has been reported for the estimation of saponins, 13 tannins, 14 flavanol derivatives, 15 proanthocyanidins 16 and triterpenoids. 12 Dai et al reported the qualitative and quantitative estimation of azadirachtin related limonoids (Azl) from Azadirachta indica seeds using this assay. 17,18 In their work, dichloromethane was used for the extraction of Azl from neem seeds and as a solvent for Azl during colorimetry.…”
Section: Introductionmentioning
confidence: 99%